2018
DOI: 10.1016/j.neuron.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Based Visual Short-Term Memory Is Widely Distributed and Hierarchically Organized

Abstract: Feature-based visual short-term memory is known to engage both sensory and association cortices. However, the extent of the participating circuit and the neural mechanisms underlying memory maintenance is still a matter of vigorous debate. To address these questions, we recorded neuronal activity from 42 cortical areas in monkeys performing a feature-based visual short-term memory task and an interleaved fixation task. We find that task-dependent differences in firing rates are widely distributed throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 57 publications
12
61
2
Order By: Relevance
“…5 H). Our results are also compatible with other experimental observations of increasing timescales along a cortical hierarchy (Murray et al 2014;Runyan et al 2017;Dotson et al 2018;Schmolesky et al 1998) , and furthermore show that even regions as early as V1 contain across-trial information about choice, reward, and sensory history, as previously reported in frontoparietal areas (Morcos and Harvey 2016;Scott et al 2017;Akrami et al 2018) . A gradual increase in timescales across brain areas suggest that each area may contribute incrementally to the persistence of information, and if so, our data support that this process also includes the visual cortices.…”
Section: The Accumulation Process May Be Distributed and Include A Besupporting
confidence: 92%
“…5 H). Our results are also compatible with other experimental observations of increasing timescales along a cortical hierarchy (Murray et al 2014;Runyan et al 2017;Dotson et al 2018;Schmolesky et al 1998) , and furthermore show that even regions as early as V1 contain across-trial information about choice, reward, and sensory history, as previously reported in frontoparietal areas (Morcos and Harvey 2016;Scott et al 2017;Akrami et al 2018) . A gradual increase in timescales across brain areas suggest that each area may contribute incrementally to the persistence of information, and if so, our data support that this process also includes the visual cortices.…”
Section: The Accumulation Process May Be Distributed and Include A Besupporting
confidence: 92%
“…Subsequently, PA has become the central element in theories of the neuronal mechanism of WM . To date, signatures of PA have been observed at the single‐cell level in many brain areas, species, and experimental paradigms …”
Section: Single‐cell Evidence For Persistent Activitymentioning
confidence: 99%
“…3 To date, signatures of PA have been observed at the single-cell level in many brain areas, species, and experimental paradigms. [4][5][6][7][8][9][10][11][12][13][14][15][16] In addition to much work in animal models, recent work has revealed direct evidence for PA and its relevance to WM in humans. 17,18 This work was performed as part of invasive monitoring for seizure localization, a clinical procedure for which depth electrodes with embedded microwires are implanted in human patients suffering from drugresistant epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…In primates, working memory function depends on activity in a distributed network of cortical 62 areas (Leavitt et al, 2017;Dotson et al, 2018). Within this network, sensory and association 63 areas display different activity patterns during working memory tasks, reflecting the 64 transformation of sensory input into a behavioral response across a delay (Christophel et al, 65 2017).…”
Section: Introduction 61mentioning
confidence: 99%
“…Within this network, sensory and association 63 areas display different activity patterns during working memory tasks, reflecting the 64 transformation of sensory input into a behavioral response across a delay (Christophel et al, 65 2017). For example, neurons in primary visual cortex (V1) increase their firing rate during 66 stimulus presentation, whereas neurons in the dorsolateral prefrontal cortex (DLPFC) often 67 change their activity during the delay period (Dotson et al, 2018;Yang et al, 2018;Quentin et 68 al., 2019). These regional differences might reflect the hierarchy of activity timescales observed 69 in the primate neocortex (Murray et al, 2014).…”
Section: Introduction 61mentioning
confidence: 99%